A one-pot radioiodination of aryl amines via stable diazonium salts: preparation of 125I-imaging agents. Issue 80 (29th August 2017) - Sloan, Nikki L.; Luthra, Sajinder K.; McRobbie, Graeme; Pimlott, Sally L.; Sutherland, Andrew
Abstract : A mild, general and efficient one-pot tandem process that produces radioiodinated SPECT imaging agents from readily available aryl amines via stable diazonium salts has been developed. Abstract : An operationally simple, one-pot, two-step tandem procedure that allows the incorporation of radioactive iodine into aryl amines via stable diazonium salts is described. The mild conditions are tolerant of various functional groups and substitution patterns, allowing late-stage, rapid access to a wide range of 125 I-labelled aryl compounds and SPECT radiotracers.